Thermal and mechanical properties of mortars reinforced with recycled brass fibres - Jose Norambuena-Contreras (Construction and Building Materials, 2021)
This paper aims to encourage the circular economy and merge the manufacturing and the construction industries, providing waste fibres from the electrical discharge machining of the former as raw material for the latter. The research analyses the effect on the physical, thermal and mechanical properties of mortars reinforced with brass fibres. The manuscript deals with different fibre length (10 mm, 15 mm and 25 mm) in variable percentages (0.5%, 1%, 2% and 4%). Larger amounts and longer fibres tend to increase the thermal conductivity whereas post cracking flexural strength is more dependent on fibre length.